2009
DOI: 10.1111/j.1365-2036.2009.03992.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete recovery of intestinal mucosa occurs very rarely in adult coeliac patients despite adherence to gluten‐free diet

Abstract: SUMMARY BackgroundExpected benefits of gluten-free diet (GFD) in coeliac patients include healing of small intestinal mucosa, but it remains unclear to what extent this benefit is achieved in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
160
3
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(180 citation statements)
references
References 44 publications
(86 reference statements)
13
160
3
4
Order By: Relevance
“…However, the linkage to intestinal damage and resolution of symptoms are strongly evident in symptomatic celiac disease patients (Carroccio, et al, 2008). One study reported patients that followed gluten-free diets always had partial remission periods but still expressed high numbers of IELs (Lanzini, et al, 2009). In the retrospective study, Lanzini and colleagues (2009) also found that architectural normalization occurred but mucosal abnormalities still persisted in adults with celiac disease; they proposed that complete normalization occurs in only 8% of adults while 65% had periods of normalization with remission, and 1% had complete deterioration of the villi even after following a gluten-free diet.…”
Section: Chapter II Review Of Literature Celiac Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…However, the linkage to intestinal damage and resolution of symptoms are strongly evident in symptomatic celiac disease patients (Carroccio, et al, 2008). One study reported patients that followed gluten-free diets always had partial remission periods but still expressed high numbers of IELs (Lanzini, et al, 2009). In the retrospective study, Lanzini and colleagues (2009) also found that architectural normalization occurred but mucosal abnormalities still persisted in adults with celiac disease; they proposed that complete normalization occurs in only 8% of adults while 65% had periods of normalization with remission, and 1% had complete deterioration of the villi even after following a gluten-free diet.…”
Section: Chapter II Review Of Literature Celiac Diseasementioning
confidence: 99%
“…Early intervention with children usually results in complete mucosal healing (Lanzini, et al, 2009), and if detected before puberty, peak bone mineral density can still be reached (Capriles, et al, 2009). Adolescents generally present with symptoms of dermatis herpetifromis and symptoms of abdominal discomfort; they have a good chance of bone remineralization assuming they follow a gluten-free diet (Capriles, et al, 2009).…”
Section: Chapter II Review Of Literature Celiac Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Persistent celiac disease activity with elevated celiac disease-specific autoantibodies, inflammation, and/or villous atrophy is not unusual in patients taking an ostensibly gluten-free diet. 7,8 There are conflicting reports regarding whether such persistent mucosal injury is associated with increased mortality in patients with celiac disease. 9,10 Considering all these issues, other strategies beyond a strict gluten-free diet alone are highly sought after by patients with celiac disease.…”
mentioning
confidence: 99%
“…2 Secondly, the excellent rate of mucosal healing after only 6-8 months of strict gluten avoidance in the coeliac group has not been so commonly reported, especially among adults. 3 It could be speculated that these patients perhaps had a relatively recent onset of disease, thus questioning whether the study findings are generalisable for the whole Italian coeliac population prior to diagnosis, who may theoretically have a better lipid profile -regardless of the inflammation markers -and both normal IMT and EDD.…”
mentioning
confidence: 99%